Molecular Mechanics Based Study of Molecular Orbitals of Cobalt(II) Halides - SINGH, R.K.; SHARMA, P.D.; SINGH, P.P. (Asian Journal of Chemistry, 2010)
The quantitative nature of contributions of atomic orbitals in the formation of molecular orbitals with the help of LCAO approximations have been studied using eigenvector values. The contribution of electrons in each occupied molecular orbitals has been calculated by adopting the population analysis method of Mulliken. The overlap population analysis has also been made to identify the bonding, non-bonding and antibonding nature of molecuIar orbital. The results indicate that in bonding between cobalt and halogens, 3dx2-y2 and 3dxy orbitals of cobalt are the main contributors in all the three halides; the next contributors are 3dxz and 4s orbitals. The 4p orbitals have a negligible role in bonding. The nonbonding orbitals in chloride are 9th and 10th, in bromide 7th and 8th and in iodide 6th and 7th molecular orbitasl. The magnitude of splitting of d orbital as evaluated by eigenvalues and eigenvector values indicate the following order: CoCl2 < CoBr2 < COI2·